2022
DOI: 10.1101/2022.03.08.483539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inter-microscope comparability of dental microwear texture data obtained from different optical profilometers

Abstract: Dental microware texture analysis has become a well-established approach for dietary inference and reconstruction of mammals and other tetrapods, both extant and extinct. As the amount of available data grows immensely, researchers could benefit from combining data gathered by others to perform meta-analyses. However, different devices used to capture three-dimensional surface scans for DMTA are known to produce variation even when measuring the same surface. Here we compare DMTA data of 36 guinea pigs that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Supplementary material is available online [47]. royalsocietypublishing.org/journal/rsfs Interface Focus 14: 20230065…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary material is available online [47]. royalsocietypublishing.org/journal/rsfs Interface Focus 14: 20230065…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, absolute parameter values are not immediately comparable. In a pilot study, Winkler & Kubo [ 43 ] showed that inter-microscope differences exist when scanning the same dataset. But they also showed that even though parameter values differ, relative differences between diet groups are consistently reproduced on different microscopes.…”
Section: Discussionmentioning
confidence: 99%